2021
DOI: 10.1111/cdoe.12702
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness and efficacy of fluoride varnish for caries prevention in South African children: A cluster‐randomized controlled community trial

Abstract: Objectives: This cluster-randomized controlled community trial aimed to assess the efficacy and costs of fluoride varnish (FV) application for caries prevention in a highrisk population in South Africa.Methods: 513 children aged 4-8 years from two schools in a township in South Africa were randomly allocated by class to the FV or Control (CO) groups. In addition to supervised toothbrushing with fluoridated toothpaste in both groups, FV was applied in 3-month intervals by trained local non-professional assistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…One RCT reported a 49% reduction in dental caries (P< 0.001) in high-risk pre-school children receiving fluoride varnish four times in Kosovo [25]. Two other high-quality trials reported a modest non-significant reduction in the worsening of d3mft in a low socioeconomic nursery setting in Scotland [13]; and no significant caries-preventive effect in a primary school setting within a high-risk community in South Africa [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One RCT reported a 49% reduction in dental caries (P< 0.001) in high-risk pre-school children receiving fluoride varnish four times in Kosovo [25]. Two other high-quality trials reported a modest non-significant reduction in the worsening of d3mft in a low socioeconomic nursery setting in Scotland [13]; and no significant caries-preventive effect in a primary school setting within a high-risk community in South Africa [26].…”
Section: Resultsmentioning
confidence: 99%
“…One RCT reported a 49% reduction in dental caries (P< 0.001) in high-risk pre-school children receiving fluoride varnish four times in Kosovo [25]. Two other high-quality trials reported a modest non-significant reduction in the worsening of d3mft in a low socioeconomic nursery setting in Scotland [13]; and no significant caries-preventive effect in a primary school setting within a high-risk community in South Africa [26]. A more recent fluoride varnish review -not restricted to education settings, which was rated as moderate quality, showed a modest and uncertain anti-caries effect in pre-schoolers and called for more costeffectiveness analyses [27].…”
Section: Fluoride Varnish Applicationmentioning
confidence: 99%
“…While the articles [34,49] were about similar results, the articles [43,48] represented the baseline study [43] and the follow-up study with final clinical trial results [48]. Of the 24 articles included in the systematic review, 17 articles could be classified as prevention [18,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]49]. Seven studies were classified as restoration [42][43][44][45][46][47][48].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were classified chronologically according to their country of study conduct, number of study participants, location (e.g., practice/clinic) of study conduct, age of study participants, and study quality assessment. Furthermore, included studies were classified into two main groups of prevention according to their primary outcome [18,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and restoration [42][43][44][45][46][47][48] with different subgroups divided at prevention (outreach/education/education, sealing, fluoride varnish, and silver diamine fluoride (SDF) and atraumatic restorative treatment (ART) as well as restoration (filling and crown). For ease of synthesis and clarity, the results were summarized in tables.…”
Section: Data Sources Search Strategy and Study Selectionmentioning
confidence: 99%
“…In the United States, the close relationship between dentists and community centres, as well as the strong cooperation and communication between doctors and policy supporters and the eligibility recognition of Medicaid issued by the government, effectively ensures the stable implementation of this recommended intervention [ 22 ]. However, a study from South Africa evaluated the effectiveness of FV in preventing caries among high-risk populations, revealing that, in addition to daily supervised tooth brushing, regular FV application had no significant effect on caries prevention [ 23 ]. This may be due to differences in national contexts and disparities between communities, as many countries and regions are still unable to effectively implement this approach [ 9 , 24 ].…”
Section: Discussionmentioning
confidence: 99%